THE INFLUENCE OF ENVIRONMENTAL SOCIAL GOVERNANCE (ESG) ON FINANCIAL PERFORMANCE WITH AUDIT QUALITY AS A MODERATION IN LISTED HEALTH SECTOR COMPANIES ON THE IDX IN 2021-2023 - Al Haetami, Muhammad Ibnu Hajar; Rifandi, Muhamad; Aji, Seto Satriyo Bayu (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Environmental, Social, and Governance (ESG) implementation on the financial performance of health sector companies listed on the Indonesia Stock Exchange in the 2021-2023 period, with audit quality as a moderating variable. This study measures financial performance using ROA, EVA, and Tobin's Q indicators to provide empirical evidence of the role of ESG in improving corporate sustainability and financial value. Methods: This study uses a quantitative approach with secondary data from the financial and sustainability reports of 13 healthcare sector companies selected through purposive sampling. Data analysis was conducted with regression and moderation tests, while ESG disclosure was measured based on GRI standards. Results: The results show that the implementation of ESG has a positive and significant effect on ROA, EVA, and Tobin's Q. In addition, audit quality, especially by Big Four auditors, strengthens the relationship between ESG and financial performance through increased transparency and credibility. Companies with good ESG disclosures tend to attract investors, enhance reputation, and achieve long-term profitability and sustainability. Novelty: This study contributes to the literature by integrating audit quality as a moderating factor and focusing on the healthcare sector, which remains under-researched in the context of ESG in Indonesia. The findings emphasize the importance of ESG as a key strategy for sustainable growth and stakeholder trust building.